Determination of Human Development Index Based on Classification of Indonesian Women in 2015-2023 (West Science Interdisciplinary Studies, 2024)
Gender equality and women’s empowerment are key elements in achieving sustainable social, economic and cultural development. This research aims to analyze the factors that influence the Human Development Index (HDI) of women in Indonesia using a multiple regression model. The independent variables used in this research are the percentage of women’s poverty (X1) and women’s life expectancy (X2), which were chosen based on their relevance to improving women’s quality of life. The data used is sourced from the Indonesian Central Statistics Agency and covers the relevant period for analysis. The analysis tool uses multiple regression. This research evaluates the extent to which these two variables influence women’s HDI in Indonesia. The results of the analysis show that variables X1 and X2 have different influences on women’s HDI. Based on the research results, it is recommended that women’s development policies focus more on reducing poverty, increasing access to education for women of productive age, and improving the quality of life to increase women’s life expectancy. This research provides insight for policy designers in formulating more effective programs to improve the quality of life of women in Indonesia.